Noninvasive Focused Ultrasound Stimulation Can Modulate Phase-Amplitude Coupling between Neuronal Oscillations in the Rat Hippocampus - Yuan, Yi; Yan, Jiaqing; Ma, Zhitao; Li, Xiaoli (Frontiers in Neuroscience, 2016)
Noninvasive focused ultrasound stimulation (FUS) can be used to modulate neural activity with high spatial resolution. Phase-amplitude coupling (PAC) between neuronal oscillations is tightly associated with cognitive processes, including learning, attention and memory. In this study, we investigated the effect of FUS on PAC between neuronal oscillations and established the relationship between the PAC index and ultrasonic intensity. The rat hippocampus was stimulated using focused ultrasound at different spatial-average pulse-average ultrasonic intensities (3.9 W/cm2, 9.6 W/cm2, and 19.2 W/cm2). The local field potentials (LFPs) in the rat hippocampus were recorded before and after FUS. Then, we analyzed PAC between neuronal oscillations using a PAC calculation algorithm. Our results showed that FUS significantly modulated PAC between the theta (4-8 Hz) and gamma (30-80 Hz) bands and between the alpha (9-13 Hz) and ripple (81-200 Hz) bands in the rat hippocampus, and PAC increased with incremental increases in ultrasonic intensity.